Developing Virtual Reality-Based Interactive Learning Media to Strengthen Islamic Character Values in Early Childhood Education - Siti Labiba Kusna; Ahmad Farid Utsman (Universitas Al-Hikmah Indonesia, 2026)
This study was conducted to address the challenge of underdeveloped Islamic character values among early childhood learners, which is influenced by limited instructional media and the high exposure to inappropriate digital content. Conventional teaching methods have not been able to present moral values in ways that are concrete, engaging, and meaningful for young learners, thus highlighting the need for an immersive technology-based innovation. This research aims to develop and evaluate a Virtual Reality–based interactive learning media designed to strengthen key Islamic character values, including prayer discipline, honesty, trustworthiness, and tolerance. The study employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Media expert validation resulted in a feasibility score of 93.33 percent, while the material expert scored the product at 90 percent, indicating that the media is highly feasible. Implementation with early childhood learners showed an improvement in character scores from an average of 65.75 in the pretest to 83.54 in the posttest, with consistent behavioral enhancement demonstrated by all participants. The findings confirm that Virtual Reality provides a concrete, engaging, and meaningful learning experience that effectively supports the internalization of Islamic values. This research contributes to the development of innovative instructional media relevant to contemporary Islamic education and offers a foundation for integrating immersive technologies into character learning at the early childhood level.